Efektivitas Sistem Reward dan Recognition terhadap Retensi Manajemen dan Tenaga Kesehatan di JEC Eye Hospitals & Clinics - Annisa, Devina Nur; Anindyah, Gabriella (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Employee retention is one of the most challenging issues in the healthcare industry, especially in hospitals. With the vast growth of hospitals and the declining growth rate of healthcare workers (medis and non medics), hospitals need to prioritize in employee retention to reduce their turnover, since a high turnover disturbs the stability, cost and quality of the services in the hospital. This study analyses the effect of two independent variables, which are the reward and recognition system to employee retention. Data collection is done through a questionanaire conducted in a purposive sampling manner. The sample used in this study were employees in JEC Eye Hospitals and clinics with a total of 70 respondents. The data analysis method is partial least squares regression. The result of this study indicate that the reward system positively influences the employee retention of JEC Eye Hospital and Clinics. These variables give a contribution of 33.6% of employee retention, while the remaining 66.4% is influenced by variables outside of this study.